Orthodontic and periodontal health interplay: insight from a case series - Saad, Noor Asyikin; Ariffin, Farha (IIUM Journal of Orofacial and Health Sciences, 2025)
Orthodontic treatment improves dental aesthetics and function but may presents challenges in patients with compromised periodontal health. This case series highlights the importance of interdisciplinary care and patient compliance in managing these complexities. Three female patients aged 27 to 42 years old with histories of orthodontic treatment were referred to Periodontology Postgraduate Clinic for further periodontal management. All patients showed periodontal deterioration post-orthodontic treatment, with complications such as gingival inflammation, deep probing pocket depth (PPD), increased tooth mobility and severe bone loss involving lower incisors. Improper plaque control and non-compliance with retainers may contributed to these outcomes. All patients reported being unaware of their periodontal issues prior to this except the ones affected by tooth mobility. Following thorough periodontal examination, each patient was informed about the importance of proper plaque control and regular maintenance visits especially in patients with any appliance intraorally, as these appliances would promote bacterial plaque retention. The patients were then received non-surgical periodontal therapy, with regular follow-ups before periodontal stability achieved. This case series emphasizes the need for early periodontal screening, continuous monitoring, and interdisciplinary collaboration between orthodontists and periodontists. Patient compliance is crucial to prevent periodontal complications and to achieve optimal functional and aesthetic results during orthodontic therapy.